(untitled) (Terr@ Plural, 2022)
This paper investigated the household practices developed in the disposal of waste in the city of Mossoró, RN, during the pandemic period. Through an online form with 16 open and closed questions, the research reached 71 people in 21 different neighborhoods and the rural area of the municipality. It was found that most respondents did not know about the selective collection service in their neighborhoods or place of residence, as well as lacked knowledge about the separation of waste. Furthermore, 57% of the people stated that there was an increase in household waste during the pandemic, with 26% pointing to an increase in organic waste and plastic packaging. It is clear, therefore, the importance of the performance of the state and municipal sphere in the management of solid waste and compliance with the National Solid Waste Policy (PNRS). Strategies for the operationalization of socio-environmental policies must also be developed in times of crisis, since the selective collection was paralyzed during the COVID-19 pandemic, harming the associations of recyclable waste pickers and the management of solid waste, since this material ended up in the local landfill.